ANALYSIS OF THE BUSINESS DEVELOPMENT STRATEGY OF SISI BASISIR RANAI NATUNA EATING HOUSE FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Sunandar Alam Sah; Nikmatul Rahmah Isnaniah; Nurdian Setiawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Despite extensive studies highlighting formal strategic planning and digital transformation as drivers of SME sustainability, little is known about how community-based enterprises survive without such mechanisms. This study examines the business development strategy of a small, family-run culinary enterprise in Ranai, Natuna Regency, that has sustained profitable operations for more than two decades without formal business planning, halal certification, or digital marketing. The research aims to describe how this strategy has actually been practiced in the field and to evaluate the extent to which its underlying practices align with Islamic economic principles, particularly maqasid al-shariah. A qualitative single case study design was employed, with data collected through in-depth interviews with the owner and long-serving staff, direct field observation, and documentation review, then analyzed thematically and triangulated across sources. Findings reveal that the enterprise's continuity is driven by an emergent, uncodified strategy centered on a narrow but consistent menu, trust-based human resource management, and a distinctive practice of offering its premises free of charge for community gatherings and celebrations, generating revenue solely from food consumption. These informal practices reflect substantive, though unstructured, alignment with Islamic values of public benefit and mutual cooperation. The study concludes that grassroots, community-embedded business models can achieve sustainable success independent of formal strategic instruments, offering meaningful implications for inclusive economic resilience in Indonesia's frontier regions in support of the Sustainable Development Goals.